Perception of the Islamic ruling on smoking among muslim adults in Malaysia; a preliminary survey - Che Abdullah, Shahrin Tarmizi; Mohd Shah, Azarisman Shah; A.M., Puteri Melor; Ab Rahman, Jamalludin; How, Soon Hin (Faculty of Medicine, International Islamic University Malaysia, 2007)
Introduction: Smoking is prevalent among Muslims in this country despite public knowledge regarding smoking as haram (unlawful). This may be due to ignorance of the consensus of the ' mufti ' on the ' fatwa ' on smoking or a result of poor education and understanding of health-related risks of smoking.